Computational methods and clinical applications for spine imaging : third International Workshop and Challenge, CSI 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015, Proceedings /: third International Workshop and Challenge, CSI 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015, Proceedings. (2016) - Unknown
No abstract available